Inhibition of TRPC1-dependent store-operated calcium entry improves synaptic stability and motor performance in a mouse model of huntington's disease - Wu, Jun (2018)
Fil: Wu, Jun. University of Texas. Southwestern Medical Center. Department of Physiology; Estados Unidos